Music Modulates Autonomic Nervous System Activity in Human Fetuses - Massimello, Francesca; Billeci, Lucia; Canu, Alessio; Montt-Guevara, Maria Magdalena; Impastato, Gaia; Varanini, Maurizio; Giannini, Andrea; Simoncini, Tommaso; Mannella, Paolo (Frontiers in Medicine, 2022)
Context Fetal Autonomic Nervous sysTem Evaluation (FANTE) is a non-invasive tool that evaluates the autonomic nervous system activity in a fetus. Autonomic nervous system maturation and development during prenatal life are pivotal for the survival and neuropsychiatric development of the baby. Objective Aim of the study is to evaluate the effect of music stimulation on fetal heart rate and specific parameters linked to ANS activity, in particular fetal heart rate variability. Methods Thirty-two women between the 32nd and 38th week with a singleton uncomplicated pregnancy were recruited. All FANTE data collections were acquired using a 10-derivation electrocardiograph placed on the maternal abdomen. In each session (5 min basal, 10 min with music stimulus, and 5 min post-stimulus), FANTE was registered. The music stimulus was “Clair de lune” Debussy, played through headphones on the mother’s abdomen (CTR: 31927). Results Music does not change the mean value of fetal heart rate. However, indices of total fetal heart rate variability statistically increase (RRsd p = 0.037, ANNsd p = 0.039, SD2 p = 0.019) during music stimulation in comparison to the basal phase. Heart rate variability increase depends mainly on the activation of parasympathetic branches (CVI p = 0.013), meanwhile, no significant changes from basal to stimulation phase were observed for indices of sympathetic activity. All the parameters of heart rate variability and parasympathetic activity remained activated in the post-stimulus phase compared to the stimulus phase. In the post-stimulus phase, sympathetic activity resulted in a significant reduction (LFn p = 0.037). Conclusion Music can influence the basal activity of the fetal autonomic nervous system, enhancing heart rate variability, without changing fetal heart rate mean value. Music is enabled to induce a relaxation state in a near-to-term fetus, mediated by parasympathetic activation and by a parallel sympathetic inhibition.